Utilization of upper gastrointestinal tumor inpatient services affected by COVID-19 in China 2018–2021: an interrupted time series analysis - Yang, Xue; Liu, Mengying; Lu, Hui (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic has posed an unprecedented challenge to the healthcare system addressing chronic diseases, significantly affecting inpatient healthcare access. We aimed to determine the impact of COVID-19 on inpatient healthcare utilization for patients with upper gastrointestinal (UGI) tumors, which would help improve responses to medical healthcare needs under future public health emergencies.MethodUtilizing interrupted time-series analysis (ITSA), we analyzed data of UGI tumor patients from 37 medical institutions in Yangzhou from 2018 to 2021. Data were extracted from the Yangzhou City Health Information Platform in Jiangsu Province, and key indicators for analysis included demographics, clinical characteristics, and hospitalization utilization (length of hospital stay, hospital costs). The intervention point was set at January 2020, marking the onset of COVID-19.ResultSeven thousand three hundred and two cases were included in the analysis. The hospital days and total hospitalization costs decreased instantaneously by 1.60 (95%CI: −2.69, −0.51) days and 5349.04 (95%CI: −11015.66, 317.571) Yuan, respectively. During the post-pandemic period, hospital days and expenses surged, exceeding pre-pandemic levels by late 2021. The structure of medical costs has changed, with the cost of blood and consumables increasing by 345.53 (95%CI: 176.07, 514.99) Yuan and 755.23 (95%CI: −698.96, 2209.42) Yuan, respectively, at the time of the outbreak. Self-payment expense increased by 1150.77 (95%CI: –243.36,2544.91) Yuan, and reimbursement ratios slightly decreased by 0.03 (95%CI: –0.11, 0.05). Additionally, significant changes occurred in the occupational structure, health insurance utilization, and complication status of patients hospitalized with UGI tumors during the pandemic.ConclusionOur findings indicate that the outbreak did cause a reduction in the use of UGI tumor inpatient services in Yangzhou City. The COVID-19 pandemic exacerbated the disease burden among patients with UGI tumors, with significantly increased costs for blood products and consumables. The findings emphasize the need to strengthen emergency management, implement precise prevention and control measures based on the dynamics of the epidemic, and ensure the safe supply of blood products and emergency medical supplies. It is necessary to improve the primary healthcare institution system to ensure patients’ access to medical services. The COVID-19 pandemic may exacerbate health inequalities. Therefore, it is essential to optimize the medical insurance system, provide targeted subsidies to medical institutions, curb the growth of unreasonable medical costs, and offer special protection for vulnerable groups.